Fulminant Amoebic Colitis: Role of the Innate and Adaptive Immune Responses - Javier, Ventura-Juárez; Rosario, Campos-Esparza María del; Martin-H, Muñoz-Ortega; Rafael, Campos-Rodríguez (IntechOpen, 2012)
None